Canon 1692: The Proper Response to a Petition for Action against Illicit Seperation and Divorce - St. Louis-Sanchez, Anthony R. (Roman Replies and CLSA Advisory Opinions 2014, 2014)
A Catholic woman has submitted a formal petition seeking action against her Catholic spouse. The parties were married according to canonical form ten years ago, and three children were born of the union. The husband became unsatisfied with married life and unilaterally field for a civil divorce, which was subsequently granted. Now, the woman has submitted a formal petition “to purse reconciliation, to obtain a decree of separation, to obtain a decree initiating the penal process, and obtain a decree the Accused shall be warned to resume conjugal living or face ecclesiastical penalties, not excluding being denied Holy Communion […].” What is the proper response to such a petition?